Utilization of an E-Book Guide for Basic Physics Experiments on Hooke's Law Based on Niteni Nirokke Nambahi for Online Learning During the COVID-19 Pandemic - Nur Setyawan, Dhimas; Widyawati, Ani; Kusumaningrum, Betty; Yunior Erlangga, Sony (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2023)
The COVID-19 pandemic has changed instructional methods, including practical activities. This study aims to implement an e-book guide for basic physics experiments on Hooke's Law based on Niteni Nirokke Nambahi for online learning during the COVID-19 pandemic. The research method used is a posttest-only control group design, involving one control class and one experimental class. The research was conducted in the even semester of the 2020/2021 academic year. The classes involved were basic physics courses in the Science Education Program at a private university in Yogyakarta. Data on practical activity were collected through self-assessment questionnaires. Data analysis was performed using descriptive quantitative methods. The results of this study indicate that the practical activities of students in both the experimental and control classes for assembling tools and recording data had the same percentages of 100% and 87.5%, respectively, both categorized as very good. Observation activities in the control and experimental classes were 87.5% and 93.75%, respectively, also categorized as very good. Practical work was able to be conducted independently, even online, despite challenges such as network issues, electricity availability, and practical materials. Future research could continue with other practical activities such as data analysis, drawing conclusions, and communicating results.